Performance of abandoned well for groundwater recharge using canal water - GUPTA, ALOK; AGGARWAL, RAJAN; KAUR, SAMANPREET (Journal of Soil and Water Conservation, 2020)
The stress on groundwater resources is continuously increasing due to rampant use in agriculture, increasing urbanization, industrialization and population. As a result, the groundwater levels in various parts of the country are declining. Groundwater recharge is one of the water management techniques by which runoff water or excess canal water can be put into aquifer itself to replenish the groundwater reservoir. For recharging groundwater, one may use variety of methods such as abandoned well, ponds and pits. In the present study, field evaluation of groundwater recharge using canal water through abandoned well under constant head condition in an unconfined aquifer was done. This study showed that rate of recharge decreased from 9.18 l/s to 3.4 l/s with time. Major factor responsible for this reduction was the total suspended solids (TSS) of canal water. As the TSS increases, the groundwater recharge linearly decreases.